PENANGANAN SCHWANNOMA VESTIBULAR - Henry Kodrat,* Rima Novirianthy** (NEURONA, 2017)
SCHWANNOMA ARE BENIGN TUMORS THAT ORIGINATE FROM MYELINFORMING CELLS COVERING THE VESTIBULOCOCHLEAR NERVE THE TREATMENT PRINCIPLES ARE TUMOR CONTROL PRESERVATION OF HEARING AND NEUROLOGICAL FUNCTION OF THE FACIAL NERVE AND THE TRIGEMINAL NERVE